Distributed control strategy for DC microgrids based on average consensus and fractional‐order local controllers. Issue 6 (7th April 2021) - Doostinia, Mehdi; Beheshti, Mohammad T. H.; Alavi, Seyed A.; Guerrero, Josep M.
Abstract: A novel distributed secondary layer control strategy based on average consensus and fractional‐order proportional‐integral (FOPI) local controllers is proposed for the regulation of the bus voltages and energy level balancing of the energy storage systems (ESSs) in DC microgrids. The distributed consensus protocol works based on an undirected sparse communication network. Fractional‐order local controllers increase the degree of freedom in the tuning of closed‐loop controllers, which is required for DC microgrids with high order dynamics. Therefore, here, FOPI local controllers are proposed for enhanced energy balancing of ESSs and improved regulation of the bus voltages across the microgrid. The proposed control strategy operates in both islanded and grid‐connected modes of a DC microgrid. In both modes, the average voltage of the microgrid converges to the microgrid desired reference voltage. The charging/discharging of ESSs is controlled independent of the microgrid operating mode to maintain a balanced energy level. The performance of the proposed distributed control strategy is validated in a 38‐ V DC microgrid case study, simulated by Simulink real‐time desktop, consisting of 10 buses and a photovoltaic renewable energy source.